Comparison of various reactive transport simulators for geological carbon sequestration. (September 2021) - Addassi, Mouadh; Omar, Abdirizak; Ghorayeb, Kassem; Hoteit, Hussein
Highlights: Benchmark for geochemical modeling in PHREEQC, TOUGHREACT, and GEM simulators. A method to minimize discrepancies in the modeling of CO2-water-rock interactions. Thermodynamic database consistency and accurate fluid properties calculation. Workflow for batch reaction and 1D reactive transport cases. Abstract: The capabilities of reactive transport modeling codes for geological carbon sequestration have improved significantly in the past decade. Comparing different geochemical modeling codes is crucial to identify modeling discrepancies, especially when experimental validation is not feasible. However, it is challenging to consistently get comparable results, as shown in previous studies where batch reaction of CO2 storage using different simulators sometimes resulted in significant discrepancies in their outputs. In this study, we introduce and demonstrate an approach to consistently produce comparable batch-reaction modeling of kinetically controlled CO2 -water-rock interactions in PHREEQC, TOUGHREACT, and GEM, which are amongst the most widely used simulators for CO2 sequestration studies. The primary step is to assemble a thermodynamic database in PHREEQC format, with representative fluid properties for CO2 -water interaction, and carefully convert it to the format of the other simulators. We use two case studies from the literature to demonstrate our method where good matches between the outputs of all three simulators were achieved, which was not previously attained. Furthermore, limiting the discrepancies in batch-reaction models provides a consistent baseline to study the coupled mechanisms of transport and chemical reaction, which was also successfully demonstrated with a one-dimensional reactive transport model in PHREEQC, GEM and TOUGHREACT.